Damage Assessment and Management of Armyworm [Mythimna separata, Walker] in Winter Maize at Rampur, Chitwan - Shrestha, A.; Pandey, A.; Sapkota, R. (Journal of the Institute of Agriculture and Animal Science, 2018)
Mythimna separata Walker commonly known as armyworm (Rice Ear-Cutting Caterpillar), belonging to Lepidoptora: Noctuidae is one of the major insect pests of maize in Nepal. Application of selective pesticide is mostly used approach to control the pest population to minimize its possible damage. A field experiment was carried out to find out the loss by armyworm in maize field (variety RML32/17) during winter season of 2016/17. The experiment was laid under Randomized Complete Block Design with eight treatments and three replications in the research field of National Maize Research Program (NMRP), Rampur. The treatments consisted of: i) Metarrhizium anisopliae ii) Nuclear Polyhedrosis Virus iii)Spinosad iv)Furadon v) Magik vi)Lara-909 vii) Multineem viii) Control. The treatments were applied three times at 30DAS, 45DAS and 60DAS for each replication and armyworm damaged plants were counted after a week of application among the 30 sample plants tagged in each plot. Number of damaged plants by armyworm after each spraying and maize yield in each plot were recorded and analyzed by GenStat. It was found that least number of plants were damaged in plots applied with treatments Lara-909, subsequently followed by Spinosad while more plants were damaged successively in control and M. anisopliae. The highest average yield (6.73 ton/ha) was found in Lara-909 treated plot followed by Spinosad (6.67 ton/ha) which were significant with the lowest average yield found in control (5.76 ton/ha) but only statistical at par with rest of the treatments. Spinosad (Natural product of Saccharopolyspora spinosa) was found to be the best alternative of chemical pesticides for the eco-friendly management of armyworm.